Charting Futures: A Comprehensive Review of Guided Pathways in Undergraduate Programs for Career Selection using Machine Learning - Trivedi, Ami; Thakkar, Tejas; Patel, Palak; Patel, Mayur (International Journal of Intelligent Systems and Applications in Engineering, 2024)
for unintentional deviations from the prescribed paths to completion. Additionally, success is enhanced when these programs have fewer bureaucratic obstacles, facilitating a smoother journey for students without unnecessary circumnavigation efforts. Resilience, within the realm of learning, is a complex concept encompassing an individual’s ability to both generate and optimize opportunities while also responding positively to setbacks and challenges. The cultivation of students’ resilience is gaining significance, supported by research demonstrating its connections to achievement, retention, engagement, and employability. Despite this recognition, there is a paucity of research investigating the specific elements of curricula that contribute to resilience and, more specifically, the distinctive role played by active learning frameworks in attaining this objective. This research presents a review that aids in comprehending the diverse facets of structure within community college career and technical programs. This paper serves as a valuable resource for practitioners engaged in program and policy design. Furthermore, it offers researchers a tool to gauge the adoption and effects of approaches characterized by a relatively higher degree of structure.